Accidental sulfur mustard exposure: A case report. (1st September 2018) - Schmidt, Annette; Steinritz, Dirk; Rudolf, Klaus-Dieter; Thiermann, Horst; Striepling, Enno
Highlights: No comparable casuistic of patients who have come into contact with sulfur mustard. Well illustrated paper of a problem rarely encountered in western societies. Case report of accidental exposure to SM in a laboratory setting. Abstract: The clinical progression following a sulfur mustard-induced skin exposure is well documented in the literature. Upon skin contact and a characteristic latency period, sulfur mustard (SM) causes erythema, blister formation and ulceration, which is associated with wound healing disorders that may require surgical treatment. Here, we present a case report of accidental exposure to SM in a laboratory setting which required surgical treatment of the skin. The case was illustrated at close intervals over a period of two years and underlines that exposure to SM has to be taken into account when typical clinical symptoms occur. Moreover skin grafts appear to be effective in SM-induced non healing skin ulcerations.